Total laparoscopic gastropexy using 1 simple continuous barbed suture line in 63 dogs1. Issue 2 (19th December 2016) - Takacs, Joel D.; Singh, Ameet; Case, J. Brad; Mayhew, Philipp D.; Giuffrida, Michelle A.; Caceres, Ana V.; Fox‐Alvarez, W. Alexander; Runge, Jeffrey J.
Abstract: Objective: To describe the use and outcome of a single, simple continuous, barbed suture line for prophylactic, total laparoscopic gastropexy in dogs. Study Design: Multi‐center, retrospective case series. Animals: Sixty‐three client‐owned dogs. Methods: Medical records of dogs undergoing total laparoscopic gastropexy using a barbed suture at 4 academic veterinary hospitals from 2011‐2015 were reviewed. Data collected included signalment, procedure time, procedure‐associated complications, short‐term complications, and long‐term outcome. All procedures were performed under general anesthesia in dorsal to dorsal‐left oblique recumbency. Laparoscopic ports were placed on ventral midline in 1 of 3 port configurations, and 5 mm laparoscopic needle drivers were used for intracorporeal sutured gastropexy with unidirectional barbed suture. The gastropexy was positioned just caudal to the 13th rib, 2‐4 cm lateral to the rectus abdominis muscle. Results: Sixty‐three dogs underwent total laparoscopic gastropexy with a single, simple continuous, barbed suture line. Median gastropexy surgery time was 70 minutes (interquartile range [IQR] 60‐90 minutes). One dog sustained splenic laceration from Veress needle penetration during initial abdominal insufflation. Short term (>24 hours to 6 months postoperative) complications included incisional seroma formation (n = 2) and suture reaction (n = 1). Long term (>6 months postoperative) complications included intermittent regurgitation and chronic diarrhea in 1 dog. Fifteen dogs had postoperative ultrasound and all had intact gastropexy sites. Conclusion: Total laparoscopic barbed gastropexy using a single, simple continuous, barbed suture line in dogs is safe and results in an intact gastropexy long term.